(untitled) (Global Journal of Science Frontier Research, 2020)
The dynamics of ethanol production of wine yeasts were examined in model experiments as well as in the winery. The ethanol concentration in young wines fermented by local strains of Saccharomyces cerevisiae, S. uvarum or Starmerella bacillaris (21, 2 and 2, respectively) did not vary considerably (c.v. 1.9 %). All of them produced significantly higher amount of ethanol than the type strain [ATCC 26108] of S. cerevisiae. However, their performance during the fermentation process diverged significantly. Thus the lag phase varied between 33 and 123 hours, while the time requested to produce half of the final ethanol concentration varied between 67 and 294 hours.